Ground-Penetrating Radar for delineation of hydraulically significant layers in the unsaturated zone of the Gnangara Mound, WA - Strobach, Elmar; Harris, Brett; Dupuis, Christian; Kepic, Anton; Martin, M. (CSIRO Publishing, 2010)
For sustainable water management, understanding shallow aquifers and the unsaturated zone is critical. Therefore the spatial distribution of hydraulic properties is of great interest for development of accurate recharge distribution models. Logging of shallow boreholes and measurements made on soil samples provide an insight into hydraulic properties with depth. However, they do not provide an adequate image of the spatial variations of key parameters. This may lead to erroneous assumptions about overall distribution of soil properties. In this study,we illustrate how Ground Penetrating Radar (GPR) can be used to image layers that impede the recharge of shallow aquifers.We discuss some of the different attributes of these layers and show how these can be characterized by Ground Penetrating Radar over the Gnangara Mound. Several hundred line kilometres of GPR have been acquired over the Gnangara Mound. Water retentive layers are easily identified and differentiated from the regional water table within the GPR sections. However, it is difficult to constrain the local 3D nature and the lateral extent of these layers from the very long sparse 2D GPR transects. Small pseudo 3D surveys at key locations have been completed. We demonstrate how these small pseudo 3D GPR surveys reveal the local consistency of water retentive layers and how the small high density surveys help understand the distribution of shallow hydraulic properties along the long transects.